2015
DOI: 10.12659/msm.892405
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Single Brain Metastasis from Non-Small Cell Lung Cancer Equally Benefit from Stereotactic Radiosurgery and Surgery: A Systematic Review

Abstract: BackgroundThe appropriate treatment of non-small cell lung cancer (NSCLC) with single brain metastasis (SBM) is still controversial. A systematic review was designed to evaluate the effectiveness of neurosurgery and stereotactic radiosurgery (SRS) in patients with SBM from NSCLC.Material/MethodsPUBMED, EMBASE, the Cochrane Library, Web of Knowledge, Current Controlled Trials, Clinical Trials, and 2 conference websites were searched to select NSCLC patients with only SBM who received brain surgery or SRS. SPSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 31 publications
2
14
0
2
Order By: Relevance
“…According to current guidelines [ 23 , 24 ], resection of solitary brain metastasis is a valuable treatment option, resulting in a five-year survival rate of 20-25% if radical surgery of the primary tumor is also performed [ 25 ]. In agreement with a recent systematic review [ 26 ], survival improves when both the primary lung tumor and brain metastasis are resected; thus, removal of the primary site and single brain metastasis appears to be an effective treatment for long-term survival. However, effective tools for selecting patients who may benefit from surgical resection of brain metastasis remain to be identified.…”
Section: Discussionsupporting
confidence: 88%
“…According to current guidelines [ 23 , 24 ], resection of solitary brain metastasis is a valuable treatment option, resulting in a five-year survival rate of 20-25% if radical surgery of the primary tumor is also performed [ 25 ]. In agreement with a recent systematic review [ 26 ], survival improves when both the primary lung tumor and brain metastasis are resected; thus, removal of the primary site and single brain metastasis appears to be an effective treatment for long-term survival. However, effective tools for selecting patients who may benefit from surgical resection of brain metastasis remain to be identified.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, a system review summarized the clinical evidence in patients with single brain metastasis from NSCLC who underwent surgical resection and SRS. 19 The results were consistent with those of the present study, which demonstrated comparable local control of brain metastases and OS benefits.…”
Section: Discussionsupporting
confidence: 92%
“…A study in two major institutions [27] in carcinoid patients with bone and/or liver metastases confirmed that coexistence of bone and liver metastasis was indicative of worse prognosis with a significant difference in overall survival -the small total numbers of patients (691) might have made it more difficult to obtain statistical significance in other histologies. The poor prognosis of brain metastases is not unexpected and is consistent across different tumor types, such as breast [28,29], lung [30], gastrointestinal [31] and ovarian [32]. It is usually measured in matters of months and may reflect the virulence of the tumor, the severity of CNS dysfunction or the inability of most current therapies to cross the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%